Options for improved livestock activity data collection and management to support measurement, reporting and verification (MRV) in Ethiopia - Wassie, Shimels Eshete; Tadesse, Million; Baker, Derek; Wilkes, Andreas; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To complement an ongoing CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) project ‘Enhancing capacities for MRV of sustainable livestock action in East Africa (Kenya and Ethiopia)’, which is implemented by UNIQUE forestry and land use, the Australian Centre for International Agricultural Research (ACIAR) supported CCAFS to implement a Small Research Activity (SRA) entitled ‘Building capacities for an integrated livestock MRV system in Ethiopia’. The objective of the SRA was to support Ethiopian stakeholders to improve the methods and procedures used to produce and manage the livestock activity data required for measurement, reporting and verification (MRV) of greenhouse gases (GHG) in Ethiopia. This report summarizes the main results of the project’s activities and the activity data collection and data management methods recommended for use in Ethiopia. These findings may be relevant to livestock MRV in other countries in East Africa and elsewhere. Section 1 explains the focus of the research activities on livestock activity data in Ethiopia. Ethiopia has identified livestock as a key subsector for GHG mitigation. An advanced livestock GHG inventory has been compiled using the Tier 2 method. However, some gaps remain in terms of data availability and data quality. The pilot activities were designed to fill those gaps, and thus enable Ethiopia to better quantify livestock GHG emissions and emission reductions in line with its national commitments on climate change. Section 2 describes the data collection tools and data management methods tested and the results. The data collection tools focused on collecting improved data on diet composition, milk yield and manure management activity data. A further pilot involved the Ethiopian Institute for Agricultural Research (EIAR) in analyses and communication of data. Section 3 highlights key recommendations for the adoption of the tools and data management activities evaluated by stakeholders. It also provides some reflections on the piloting process from the project team, which may provide some guidance for future piloting of MRV innovations elsewhere in East Africa. Section 4 presents the manual’s purpose for each production system to guide data collection procedures. It extends to guidance and pilots’ lessons learned on sampling, selection of participants, preliminary analysis, and other practical implementation issues. These enable scaling up of the use of the piloted tools to regional and national levels.